2021
DOI: 10.1186/s13229-021-00425-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased aperiodic gamma power in young boys with Fragile X Syndrome is associated with better language ability

Abstract: Background The lack of robust and reliable clinical biomarkers in Fragile X Syndrome (FXS), the most common inherited form of intellectual disability, has limited the successful translation of bench-to-bedside therapeutics. While numerous drugs have shown promise in reversing synaptic and behavioral phenotypes in mouse models of FXS, none have demonstrated clinical efficacy in humans. Electroencephalographic (EEG) measures have been identified as candidate biomarkers as EEG recordings of both a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 68 publications
7
73
0
Order By: Relevance
“…Recent resting-state EEG studies have shown increased resting-state power in animal models of FXS, notably in delta and gamma frequency bands (18,19). Studies with FXS adults (20), male adults (21) and young boys (22) obtained similar results. Gamma frequency bands are associated with high-level cognitive functions in healthy controls while performing cognitively demanding tasks (20,23).…”
Section: Introductionmentioning
confidence: 65%
“…Recent resting-state EEG studies have shown increased resting-state power in animal models of FXS, notably in delta and gamma frequency bands (18,19). Studies with FXS adults (20), male adults (21) and young boys (22) obtained similar results. Gamma frequency bands are associated with high-level cognitive functions in healthy controls while performing cognitively demanding tasks (20,23).…”
Section: Introductionmentioning
confidence: 65%
“…The ability of early sound exposure, but not sound attenuation, to reduce cortical hyperexcitability symptoms suggests that developmental trajectories of atypical sensory processing need to be investigated across closely spaced developmental ages. Examination of deficits at a single age or a small number of ages may miss the main cause of pathology early on, and only record manifestation of compensatory mechanisms (32,33), which may be indirectly altered by the genetic mutation and can be beneficial (111)(112)(113). 5.…”
Section: Future Studiesmentioning
confidence: 99%
“…Specifically, reductions in exponent magnitude (flatter slopes) are thought to reflect increases in E:I ratios while increases in exponent magnitude (steeper slopes) are believed to reflect decreases in E:I ratios ( Donoghue et al, 2020a , Gao et al, 2017 ). There is an increasing body of evidence to suggest that E:I imbalances are associated with neurological and psychiatric disorders such as attention-deficit/hyperactivity disorder (ADHD; Mamiya et al, 2021 ; Ostlund et al, 2021 ; Robertson et al, 2019 ) and schizophrenia ( Molina et al, 2020 ) and Fragile X Syndrome (FXS; Wilkinson and Nelson, 2021 ). This is particularly evident in instances in which pharmaceutical interventions have led to changes in E:I ratios in schizophrenia ( Molina et al, 2020 ) and possibly in ADHD ( Mamiya et al, 2021 , Robertson et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%